Control of Canine Visceral Leishmaniasis: A Success Case Based on Deltamethrin 4% Collars - Vera Lucia Fonseca de Camargo-Neves; Eliana Bravo Calemes; Lilian Aparecida Colebrusco Rodas; Fredy Galvis-Ovallos; Luis Jacintho da Silva (MDPI AG, 2021)
The effect of employing collars impregnated with deltamethrin 4% (DM4) to control canine visceral leishmaniasis (CVL) was evaluated. as were the individual factors associated with this infection. A cohort study that included household dogs was conducted between 2002 and 2006. The presence of pathognomonic signals, peridomiciliary sleep habits and breed were the main factors associated with the infection. The use of DM4 collars contributed to the reduction of CVL with an effectiveness of 66%, and the dogs' survival rate was greater than 90% at 50 months. In conclusion, the adoption of DM4 collars reduced the number of euthanized canines and in the incidence of CVL, and this reduction was sustained for one year after discontinuing the use of the collar.